Exploring the Interplay of Product Quality, Facilities, Consumer Satisfaction, and Sales Volume in Modern Markets - Adyatrin, Nabilla (KINERJA: Jurnal Manajemen Organisasi dan Industri, 2023)
This study aims to determine the effect of two independent variables, namely product quality and facilities, on consumer satisfaction and its impact on sales volume in Griya Kalibaru Housing, Depok, West Java. This study used a quantitative approach with associative research using the questionnaire method as a data collection tool. Data analysis techniques used include validity tests, reliability tests, classical assumption tests, linear regression tests, correlation coefficient tests, determination coefficient tests, hypothesis tests, path analysis, and sobel tests. The population of this study was all residents of houses in Griya Kalibaru Housing, Depok City, West Java, totaling 58 people. Using saturated sampling techniques, a sample of 58 respondents was obtained. The results showed a positive and significant influence between facilities on sales volume through customer satisfaction, with a t-statistic value of 2.911, exceeding the t-table value of 1.96, and a sig value of 0.03, smaller than the significance level of 0.05, so that Ho9 was rejected and Ha9 was accepted. In addition, the Adjusted R Square coefficient of determination of 0.701 shows that the variables of product quality, facilities, and consumer satisfaction contribute 70.1% to sales volume. The remaining 29.9% was influenced by other factors not included in the study.